1986
DOI: 10.1056/nejm198612183152503
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Non-A, Non-B Hepatitis with Recombinant Human Alpha Interferon

Abstract: We treated 10 patients who had chronic non-A,non-B hepatitis with recombinant human alpha interferon in varying doses (0.5 to 5 million units) daily, every other day, or three times weekly for up to 12 months. In 8 of the 10 patients, elevated serum aminotransferase levels decreased rapidly during therapy and eventually fell into the normal or nearly normal range. In two of these patients, the interferon therapy was stopped after four months, and in both cases, a prompt return of aminotransferase activities to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
295
2
11

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 901 publications
(312 citation statements)
references
References 12 publications
4
295
2
11
Order By: Relevance
“…Bone marrow suppression is a common side effect of interferon alfa. 32 Furthermore, patients with end-stage liver disease frequently have thrombocytopenia and/or leukopenia secondary to hypersplenism. Hypothyroidism and nausea and vomiting also are frequent side effects of this treatment in patients with noncirrhotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow suppression is a common side effect of interferon alfa. 32 Furthermore, patients with end-stage liver disease frequently have thrombocytopenia and/or leukopenia secondary to hypersplenism. Hypothyroidism and nausea and vomiting also are frequent side effects of this treatment in patients with noncirrhotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 As a main player in innate immunity against viruses, the interferon (IFN) system has a key role in curtailing pathogens by putting infected and neighboring cells into an antiviral state. 2 Also, HCV has been known for a long time to be highly sensitive to treatment with type I IFNs, 3 and still today IFN-␣ is the major component of HCV therapy. The fact that HCV is sensitive to IFN yet it manages to establish persistent infections suggested that the virus may have evolved mechanisms to circumvent detection by the innate antiviral defense system.…”
mentioning
confidence: 99%
“…The potent antiviral and antitumor activity of IFNs has been used therapeutically in humans [8], and tried in cattle [12], horses [16], and pigs [13]. Recombinant feline interferon-ω (rFeIFN-ω), produced in silkworm larvae using a baculovirus vector [27,33], has shown antiviral activity against infection with feline calicivirus, herpesvirus and enteropathogenic virus [19,35].…”
mentioning
confidence: 99%